2018
DOI: 10.1016/j.envres.2018.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Lead exposure to children from consumption of backyard chicken eggs

Abstract: Backyard chicken ownership is rapidly increasing in urban areas in the United States, largely as a way to provide eggs for household consumption. Despite elevated levels of environmental lead contamination in many US cities, the role of backyard chicken eggs as a pathway for lead exposure, particularly for children, has received limited scrutiny. To characterize lead exposure from consumption of backyard chicken eggs for children and predict related effects on blood lead level (BLL), we conducted a cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Given that exposure to lead via consumption of eggs is a significant human health threat, this finding is concerning, and flock owners, primarily pregnant women and children who are consuming eggs, should be advised of this risk and of routine testing options. 3,24,39 Most of the additional toxin-related mortalities were preventable, including rodenticide, insecticide, and ionophore exposures, and medication overdoses. One case of botulism involved the mortality of 14 chickens that had access to pecking on a backyard compost pile, which poses a newly described threat for backyard flock owners.…”
Section: Discussionmentioning
confidence: 99%
“…Given that exposure to lead via consumption of eggs is a significant human health threat, this finding is concerning, and flock owners, primarily pregnant women and children who are consuming eggs, should be advised of this risk and of routine testing options. 3,24,39 Most of the additional toxin-related mortalities were preventable, including rodenticide, insecticide, and ionophore exposures, and medication overdoses. One case of botulism involved the mortality of 14 chickens that had access to pecking on a backyard compost pile, which poses a newly described threat for backyard flock owners.…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of chips of Pb-based paint peeling from a chicken house was associated to acute poisoning of laying hens ( Trampel et al., 2003 ), whereas chronic exposure to Pb-contaminated soil has been implicated in subclinical exposure of backyard flocks ( Leibler et al., 2018 ; Mordarski et al., 2018 ). Clinical signs of acute Pb poisoning in chickens include muscle weakness, ataxia, and loss of appetite, followed by marked weight loss and eventual cessation of egg production.…”
Section: Methodological Approachmentioning
confidence: 99%
“…It has been suggested that after ingestion by hens, heavy metals can deposit in different tissues including eggs laid by hens exposed to pollution [2,8]. Therefore, assessing foods for potentially harmful toxic metals has been recently recognized as an important health issue because exposure to heavy metals can be harmful to the health of children and adults [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing exposure to environmental lead has been attributed to recent industrialization and urbanization in some regions [13,14]. Recent studies have shown that plants and grains grown upon soils contaminated with lead contained elevated levels of this toxic heavy metal [10,15,16]. Therefore, it would not be surprising that birds and animals grazing on contaminated grains would be found to have elevated levels of this toxic heavy metal [6,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation